Review on online operation insulator identification and fault diagnosis based on UAV patrol images and deep learning algorithms - Zhang, Zhaoyun; Cai, Delong; Zhang, Zhi (Frontiers in Energy Research, 2022)
Artificial intelligence has great potential in smart grid. Power system image recognition based on artificial intelligence is an important research direction. Insulator is an important equipment of power grid,which is related to the operation safety of power grid. The online operation insulator location identification and fault diagnosis technology based on UAV patrol pictures and deep learning algorithms has developed continuously and achieved a series of good results. By compiling the literature on insulator detection technology in recent years, Three common application scenarios and research difficulties are summarized: the improvement of detection accuracy and real-time speed; image recognition of complex background and target occlusion; multi-scale object and small object detection. At the same time, the improved algorithms in the literature are comprehensively summarized, the performance evaluation indexes of various algorithms are compared.